Behaviour of vertical cylindrical tank with local wall imperfections - Šapalas, Antanas; Šaučiuvėnas, Gintas; Rasiulis, Konstantin; Griškevičius, Mečislovas; Gečys, Tomas (Journal of Civil Engineering and Management, 2019)
Design of modern thin-walled metal structures is widely used around the world. In recent decades, more comprehensive research is carried out to investigate the behaviour of various thin-walled structures. Generally, the structure with regular geometry is investigated. In various countries such as USA, Russia, and the European Union issued the standards on regulation of the construction, design and maintenance of thin-walled structures.The actually used period of tanks usually is longer than recommendatory period. Recommendatory maintenance period of metal tanks is 15–20 years. Therefore, for such structures one of the most considerable questions is the residual load bearing capacity beyond the end of the maintenance period. This phase of using of structures is associated with complex investigation and numerical analysis of thin-walled structures.In this paper the load bearing capacity of the steel wall of the existing over-ground vertical cylindrical tank in volume of 5,000 m3 with a single defect and with a few contiguous local defects of the shape is analyzed. Calculations carried out are taking into account all the imperfections of the wall geometry.A major goal of the research – developing a realistic numerical model of the object analyzed, taking into account all the imperfections, determining the wall stress and strain state, exploring the places of extreme points, calculating the residual load bearing capacity of the tank and scrutinizing possible strengthening schemes for defective areas.